Pembelajaran Interaktif dan Menyenangkan di Luar Lingkungan Sekolah Melalui Bimbingan Belajar Harian - Azizah, Wilda; Nayaputri, Devina Yasintha; Nabila, Nur Qurratul; Sabila, Arina Hasya; Laksono, Ailsa Purwabhagawanta Saskirana; Simatupang, Devona Valerie; Hikmawan, Baso Didik; Junaidin, Junaidin; Ahmad, Islamudin (Jurnal Abdita Naturafarm, 2024)
This study evaluated the effectiveness of a daily home-based learning program implemented in Rumah Pintar, Pantai Lango. The program aimed to improve the academic skills of children aged 3-12 years who were experiencing learning difficulties. The intervention, conducted from July 12 to August 2, 2024, provided a structured learning environment outside of school hours. Participants were divided into groups based on their academic levels, addressing needs ranging from basic literacy and numeracy to English language learning. Results indicated that the program was successful in enhancing participants' abilities in reading, writing, and mathematics. However, challenges such as fluctuating daily attendance, attributed to a lack of parental awareness about the importance of home learning, were encountered. Despite these challenges, the program demonstrated the potential of non-formal, home-based learning initiatives in addressing the educational needs of children in underserved areas.